Education Of the Importance of Vegetable and Fruit Consumption on Students of SMA Plus PGRI Cibinong During the Covid-19 Pandemic - Mutiara Fadhillah; Inne Indraaryani Suryaalamsah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
According to the 2014 Individual Food Consumption Survey (SKMI), 77% of adolescents (13-18 years) consume vegetables, whereas 28.1 percent consume fruit. Nutrition education is one strategy for increasing understanding. Nutrition education is critical for increasing nutritional knowledge and developing favorable attitudes about nutritious foods in order to develop healthy eating habits. This community service project took place in July 2021 at SMA Plus PGRI Cibinong, Bogor. The teaching approach used was online seminars (webinars) for culinary students, which included lectures, discussions, and Q&A sessions, as well as games. Fifty students participated in community service activities. There was a 9.6 percent increase in the pre- and post-test scores. It is known that the pre-test findings of 90.4 percent increased to 100 percent when post-test results were acquired. This community service project resulted in a change, specifically increased awareness of the need of ingesting vegetables and fruit during a pandemic like COVID-19. At the start of the exercise, three students did not understand or were less capable, based on the results of the pre-test administered.